2015
DOI: 10.5539/ijms.v7n3p84
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Destination Knowledge Acquisition in Religious Tourism: Perspective of Umrah Travelers

Abstract: Religious travel has grown consistently with the growth of the tourism industry worldwide. However, some of the religious based tourism particularly pilgrimage tourism such as Umrah received little attention in the literature although there are 6 million people performing it each year. Thus, this study aims to examine the relationship between the factors influencing information acquisition behavior to gain destination product knowledge in performing Umrah. Survey data from 198 Umrah travelers were analyzed usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 37 publications
0
9
0
Order By: Relevance
“…These feelings reflect employees experience and knowledge and their capability to be confident in themselves and build confidence in customers themselves. According to (Hassan et al 2015), assurance can be developed by the level of information, knowledge and kind treatment by the employees in offering the services and their capability to build trust and confidence in Umrah customers especially in Umrah travel services (Ashdaq et al 2015). Finally, in this research, responsiveness is the readiness of Umrah travel agents at a specific period to provide punctual services as perceived by customers.…”
Section: The Relationship Between Assurance and Umrah Customer Loyaltymentioning
confidence: 99%
“…These feelings reflect employees experience and knowledge and their capability to be confident in themselves and build confidence in customers themselves. According to (Hassan et al 2015), assurance can be developed by the level of information, knowledge and kind treatment by the employees in offering the services and their capability to build trust and confidence in Umrah customers especially in Umrah travel services (Ashdaq et al 2015). Finally, in this research, responsiveness is the readiness of Umrah travel agents at a specific period to provide punctual services as perceived by customers.…”
Section: The Relationship Between Assurance and Umrah Customer Loyaltymentioning
confidence: 99%
“…The number of the studies only started to increase after the 2000s. In one study on religious tourists' information acquisition behaviours (Hassan et al, 2015), online information sources were found important for Umrah travellers. In another study, Haq and Jackson (2009) investigated the role of ICTs in religious tourists' perceptions.…”
Section: The Use Of Sm By Religious Touristsmentioning
confidence: 99%
“…While Hajj is the fifth pillar of Islam and has defined rituals from a temporal and practical standpoint, Umrah is voluntary and can be performed at any time, except on Hajj days, and maintains the practice of rituals in much the same way. In Islam, religious and spiritual journeys can be divided into three types: Hajj, Umrah, and Ziyara (Hassan et al, 2015;Haq and Wong, 2010;Timothy and Olsen, 2006). While the Umrah is part of the pilgrimage to Mecca, it is a minor pilgrimage that Muslims can undertake at any time of the year (Heidari et al, 2018), and represents a major form of travel for Muslims worldwide.…”
Section: Introductionmentioning
confidence: 99%
“…While the Umrah is part of the pilgrimage to Mecca, it is a minor pilgrimage that Muslims can undertake at any time of the year (Heidari et al, 2018), and represents a major form of travel for Muslims worldwide. It can be completed more than once (Hassan et al, 2015), and can be repeated, based on a person's physical and financial capabilities.…”
Section: Introductionmentioning
confidence: 99%